The wealth and poverty of nations why some are so rich and some so poor - Landes, David S. (New York W.W. Norton, 1999)
The Wealth and Poverty of Nations is David S. Landes's acclaimed, best-selling exploration of one of the most contentious and hotly debated questions of our time: Why do some nations achieve economic success while others remain mired in poverty? The answer, as Landes definitively illustrates, is a complex interplay of cultural mores and historical circumstance. Rich with anecdotal evidence, piercing analysis, and a truly astonishing range of erudition, The Wealth and Poverty of Nations is a "picture of enormous sweep and brilliant insight" (Kenneth Arrow) as well as one of the most audaciously ambitious works of history in decades.
xxi, 658 p. : maps ; 25 cm.
Keywords: Wealth--Europe--History.